Effects of Two Commercial Supplemental Fat Products on Body Condition Score and Cow- and Herd-Level Milk Yield and Composition in a Commercial Dairy Herd in Kansas - A. L. Scanavez; C. A. Gamarra; R. S. de Oliveira; L. G. Mendonça (Kansas Agricultural Experiment Station Research Reports, 2019)
Feeding fat supplements to lactating dairy cows is an effective strategy to increase energy density of rations and increase milk yield. However, it is not clear whether supplementing a specific fat supplement for the entire lactating herd provides better results than others in commercial dairy herds. The objective of this study was to compare the effects of fat supplementation with two commercial products on changes in body condition score (BCS) and cow- and herd-level milk production and composition in a large commercial dairy herd. The study was conducted in a herd milking approximately 1,500 Holstein cows. One of two treatments was assigned to the herd in a singlesubject crossover design with 4 periods. Treatments were inclusion of 0.24 lb/cow per day of a supplement rich in saturated fats (Propel; Propel Energy Plus) or 0.22 lb/cow per day of a supplement containing calcium salts of long-chain fatty acids (Control). Treatments were applied to all lactating cows during four consecutive weeks. Milk yield recorded during the last week of each period was used for statistical analyses. In addition, milk samples were collected in the last week of each period to determine test-day milk protein, fat, somatic cell count, and urea nitrogen concentrations. At the beginning and at the end of each experimental period, BCS was assessed from a subset of cows to evaluate BCS change. Herd-level milk fat, protein, and somatic cell count were recorded daily by the milk cooperative. Bulk tank milk fat and protein contents on the fourth week of fat supplementation were similar between Control and Propel treatments. Average milk yield during the fourth week of fat supplementation (yield recorded daily in the last week of the experimental period) was greater for Control than Propel supplementation (83.4 vs. 82.1 ± 1.7 lb/day). In the analyses that used test-day data, milk yield did not differ between Control and Propel treatments. Supplementation with Propel resulted in greater milk fat (4.50 vs. 4.29 ± 0.12%) and reduced milk protein content (3.12 vs. 3.14 ± 0.03%) compared with Control. In addition, milk urea nitrogen was reduced for Control vs. Propel cows (12.5 vs. 13.1 ± 0.04 mg/dL). Supplementation with Propel increased energy-corrected milk (93.9 vs. 91.7 ± 3.1 lb/ day) and fat-corrected milk (96.3 vs. 93.5 ± 3.3 lb/day) yields compared with Control supplementation. Proportion of cows that lost BCS during the fat supplementation periods did not differ between treatments; however, BCS change tended to be more pronounced during supplementation with Propel than Control treatment (-0.03 vs. 0.02 ± 0.04). In conclusion, fat supplementation using the Propel treatment resulted in greater milk fat content, energy-corrected milk, and fat-corrected milk compared with fat supplementation with Control. Our findings suggest that the type of market to which milk is sold should be considered in the choice of fat supplements.
Keywords: fatty acids; milk components; energy-corrected milk; fat-corrected milk